Self-reported muscle pain in adolescents with migraine and tension-type headache - Blaschek, Astrid; Milde-Busch, Astrid; Straube, Andreas; Schankin, Christoph; Langhagen, Thyra; Jahn, Klaus; Schröder, Sebastian Andreas; Reiter, Karl; von Kries, Rüdiger; Heinen, Florian (Cephalalgia, 2012)
Aim: To identify possible associations between muscular pain and headache in adolescents in a large population-based sample. Methods: Grammar school students were invited to fill in a questionnaire on headache and associated lifestyle factors. Headache was classified according to the German version of the International Classification of Headache Disorders (2nd edition). Muscular pain was assessed via denoting affected areas in schematic drawings of a body and via provoked muscular pain on controlled movements of head, neck and shoulder regions. Results: Prevalence of any headache within the previous 6 months exceeded 80%. In all subjects muscular pain or pain on movement was most prominent in the neck and shoulder region, ranging from 9% to 27% in the non-headache population to up to 63% for individuals with migraine or mixed migraine and tension-type headache (TTH). Frequency of muscular pain increased significantly with growing chronicity of TTH. Interpretation: A strong association between muscle pain in the neck/shoulder region and headache was observed, pointing to the importance of muscular pain for headache in adolescents. Also, in this age group muscular pain appears to be of particular importance in chronic TTH and – unexpectedly – in migraine, which is the most important new finding in our study.